Evolutionary divergence between two closely related species: Drosophila madeirensis and D. subobscura : quantitative genetic differentiation, reproductive barriers and evolutionary potential - Rego, Carla José Azevedo (2010)
Tese de doutoramento em Biologia (Biologia Evolutiva), apresentada à Universidade de Lisboa através da Faculdade de Ciências, 2008